Biochemical Profiles in Women with Parathyroid Carcinoma Under Chemotherapy - Zahraa Ali Nashoor Alnawas; Kawther hussein Dikain (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Parathyroid carcinoma is a rare endocrine malignancy characterized by excessive parathyroid hormone secretion and severe metabolic disruption. Specific Background: Although its biochemical profile is well documented, evidence describing how chemotherapy influences circulating calcium, phosphate, vitamin D metabolites, and trace elements—particularly among older women—remains limited. Knowledge Gap: Few studies systematically compare these biochemical alterations with healthy controls to determine the extent of treatment-associated metabolic derangement. Aims: This study evaluates and correlates key biochemical parameters in women with parathyroid carcinoma undergoing chemotherapy relative to age-matched healthy subjects. Results: Findings demonstrated significantly elevated serum calcium and parathyroid hormone, alongside reduced phosphate, 25(OH)D, 1,25(OH)₂D, zinc, and iron in the patient group, indicating marked disruptions across mineral metabolism, vitamin D dynamics, and trace element homeostasis. Novelty: The study provides one of the first integrated biochemical assessments focused exclusively on chemotreated female patients, revealing a broader metabolic signature than previously recognized. Implications: These results highlight the importance of comprehensive biochemical monitoring to improve diagnostic accuracy, evaluate treatment response, and anticipate complications, thereby supporting more precise management strategies for parathyroid carcinoma.Highlight : Elevated calcium and PTH are the key biochemical disturbances. Reduced phosphate and vitamin D indicate notable metabolic impairment. Trace element changes support the need for comprehensive biochemical evaluation. Keywords : Parathyroid Carcinoma, Hypercalcemia, Parathyroid Hormone (PTH), Vitamin D Deficiency, Hypophosphatemia